A questionnaire based study to assess the interns’ knowledge about the brand names of drugs routinely prescribed in a tertiary care hospital in Kerala, India - Krishnan, Divya G.; Ubedulla, Shaikh; Keloth, Anukesh Vasu (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The gap in the knowledge of interns between brand names, generic name and indication of a drug can lead to unwanted clinical consequences. This study was conducted to assess the knowledge of interns at a tertiary care hospital regarding the generic name and indications of the routinely prescribed brand names of drugs. Methods: In this study, interns were required to write whether they prescribed the brand names mentioned in the questionnaire in the preceding six months, their generic name and the indication for their use. Results were expressed using descriptive statistics. Results: All brands except Zovobact SB was prescribed by more than 50% of interns in the preceding six months. The generic equivalents were correctly identified by good percentage of interns for Hicet (100%), Asthalin (95%), Cifran (90%) but the percentage of correct answers was low for other brands. For combination brands, correct generic names of all components were identified by more than 50% of interns for oflox TZ (93%), Septid D (68%) and Losar H (68%). The percentage of correct response for the indication of the brands was satisfactory for Hicet (100%), Asthalin (98%), Cifran (98%), Zerodol P (100%), Cyclopam (100%), oflox TZ (100%), Losar H (98%), Septid D (98%) but was inadequate for Taxim O (48%), Betaloc (33%), Valium (23%), Diamox (0%), Quadriderm (31%) and Zovobact SB (31%). Conclusions: This study identified lacunas in the knowledge of interns regarding generic equivalents and indications of brand names. Strategies to overcome the problem should be devised to ensure patient safety.